Going public to acquire? The acquisition motive in IPOs - Celikyurt, Ugur; Sevilir, Merih; Shivdasani, Anil (Journal of Financial Economics, 2010)
Newly public firms make acquisitions at a torrid pace. Their large acquisition appetites reflect the concentration of initial public offerings (IPOs) in mergers and acquisitions-(M&A-) intensive industries, but acquisitions by IPO firms also outpace those by mature firms in the same industry. IPO firms’ acquisition activity is fueled by the initial capital infusion at the IPO and through the creation of an acquisition currency used to raise capital for both cash- and stock-financed acquisitions along with debt issuance subsequent to the IPO. IPO firms play a bigger role in the M&A process by participating as acquirers than they do as takeover targets, and acquisitions are as important to their growth as research and development (R&D) and capital expenditures (CAPEX). The pattern of acquisitions following an IPO shapes the evolution of ownership structure of newly public firms.